EXPERIMENTAL EVIDENCE FOR CA-CHLORIDE ION PAIRS IN THE INTERLAYER OF MONTMORILLONITE. AN XRD PROFILE MODELING APPROACH - Ferrage E.; Charlet L.; Lanson B.; Tournassat C.; Rinnert E. (My University, 2005)
Montmorillonite was equilibrated with high normality Cl - solutions to assess the possible presence of MeCl + ion pairs in smectite interlayers which is suggested by chemical modeling of cation exchange experimental studies. Structural modifications induced by the presence of such ion pairs, and more especially those related to smectite hydration properties, were characterized from the modeling of experimental X-ray diffraction (XRD) profiles. As compared to those obtained from samples prepared at low ionic strength, XRD patterns from samples equilibrated in high ionic strength CaCl2 solutions exhibited a small positional shift of 00
Keywords: ion pairs; montmorillonite; XRD profile modeling